Hydrogeochemical evolution and groundwater recharge processes in arsenic enriched area in central Gangetic Plain, India - Kumar, S.; Joshi, S. K.; Pant, N.; Singh, S.; Chakravorty, B.; Saini, R. K.; Kumar, V.; Singh, A.; Ghosh, N.C.; Mukherjee, A.; Rai, P.; Singh, V. (Elsevier, 2021)
The present study dealt with understanding hydrogeochemical evolution, ascertaining distribution, fate and spatio-temporal variation of arsenic along with comprehending recharge processes and quantification of recharge rate in the central Gangetic plain, India. The arsenic enriched area was observed mostly in the fluvial deposits with younger alluvium. The depth to water levels maps for 1996 and 2016 showed marked spatio-temporal variation and the groundwater recharge rate was estimated to be varied between 0.05 m/year and 0.07 m/year in the study area. The elevated arsenic concentration was noticed in the region, having declined groundwater recharge. A total of 147 water samples were collected from hand pumps (n = 141) and rivers (n = 6) during the pre-monsoon period (May 2016). In addition, about 81 groundwater samples were collected from 27 locations during the pre-monsoon, monsoon and winter 2019 for studying seasonal variability in the hydrogeochemical parameters and isotopic composition of water. Arsenic concentration was found more in the area where deposits of coarser sediment of the Quaternary period was present along the rivers Ganga and Ghaghra. The arsenic concentration was observed higher in the pre-monsoon (maxm. As 641 µg/L), followed by the post-monsoon (425 µg/L) and monsoon season (375 µg/L). The depleted isotopic value and higher D-excess values in groundwater suggested active recharge conditions with precipitation as the major source of recharge in the study area. It is hypothesized that rainwater induced oxygenated water into the aquifer by the process of recharge, which may prompted various biogeochemical reactions due to change in redox conditions and endorsed arsenic sorption in the monsoon season. Thereafter, anoxic conditions prevailed in the post-monsoon season, and finally, in the pre-monsoon season, reducing conditions continued and arsenic released at a rapid rate, which was justified with the seasonal variation of arsenic concentration.